Vancomycin-Conjugated Polyethyleneimine-Stabilized Gold Nanoparticles Attenuate Germination and Show Potent Antifungal Activity against Aspergillus spp. - Nikhil A.; Tiwari A.K.; Tilak R.; Kumar S.; Bharti P.S.; Pandey P.C.; Narayan R.J.; Gupta M.K. (My University, 2025)
Antifungal drug resistance in filamentous fungi, particularly Aspergillus species, is increasing worldwide. Therefore, new antifungal drugs or combinations of drugs are urgently required to overcome this public health situation. In the present study, we examined the antifungal activity of vancomycin-functionalized AuNPs. These functionalized AuNPs were characterized, and their antifungal activity and associated killing mechanism were investigated using conventional methodologies against the conidia of A. fumigatus and A. flavus. The differential antifungal activity of vancomycin-functionalized Au-NPs against the conidia of Aspergillus species is dependent on structural differences in the conidial cell wall. The results demonstrated potent fungicidal activity against A. fumigatus, with a MIC value of 4.68 µg/mL, 93% germination inhibition, and 38.4% killing rate within 8 h of exposure. However, the activity against A. flavus was fungistatic; a MIC value of 18.7 µg/mL and 35% conidial germination inhibition, followed by 28.4% killing rate, were noted under similar conditions. Furthermore, endogenous reactive oxygen species (ROS) accumulation was 37.4 and 23.1% in conidial populations of A. fumigatus and A. flavus, respectively. Raman spectroscopy analysis confirmed the possible (but not confirmed) binding of functionalized AuNPs with the chitin and galactomannan components of the cell wall. A potential strategy that involves the exploration of antibacterial drugs using AuNPs as efficient drug carriers may also be appropriate for countering emerging drug resistance in filamentous fungi. © 2024 by the authors.